Uma sociedade para todas as idades: processos do habitar a casa e a cidade - Maria Moura de Abreu (2016)
The present dissertation compounds chapters denominated as worlds. Despite being organized, these worlds cross and complete each other, they represent a set of ideas, considerations and inspiring case studies that are essential to the process of thought about a society for all ages1.The worlds, adopting Karl Popper's definition and applying it to this context, represent different types of analysis of the chosen subjects for the construction of that society and this dissertation: the world population aging, as the biggest problem presented by the A society for all ages contest regulation; the "ilhas" of Porto, as the "theme" chosen as a response to the contest; and the inhabit of the house and the city, as intrinsically linked actions to the previous subjects.As a result of this consideration and all the worlds coexisting, they can not be dissociated. The four themes define each world and, at the same time, links them.First we introduce the problematization world about the four themes and, as a consequence of that, the result of the study developed for the contest, the first approach of the project. Next, a more subjective view about the same four themes, as individual and collective memories that add a new counterpart in the developed creative thought process - this is the second world. The third, a proposal for a different "ilha" in Porto, as unpretentious and theoretical as the first one, acts like a result of the previous worlds, therefore, complementing them.The development process starts in the abstract, with a group of ideas for the "Ilha do Lampião", in hand with reality, with an invite for the rehabilitation of the "Bairro da Travessa da Póvoa", not bearing in mind the end goal or conclusion of the project but just the beginning - "Amo los inicios. Yo creo que el inicio es lo que garantiza la prosecución."2 - which has as much of certainties as uncertainties, as much of utopian, as necessary.